Natives and Newcomers: The ordering of Opportunity in Mid-Nineteenth Century Poughkeepsie - Stern, Mark J. (Labour / Le Travail, 1979)
This article reviews the book, "Natives and Newcomers: The ordering of Opportunity in Mid-Nineteenth Century Poughkeepsie," by Clyde Griffen and Sally Griffen.